Observation of D0−D[bar]0 oscillations - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
We report a measurement of the time-dependent ratio of D0→K+π− to D0→K−π+ decay rates in D*+-tagged events using 1.0 fb−1 of integrated luminosity recorded by the LHCb experiment. We measure the mixing parameters x'2=(−0.9±1.3)×10−4, y′=(7.2±2.4)×10−3, and the ratio of doubly-Cabibbo-suppressed to Cabibbo-favored decay rates RD=(3.52±0.15)×10−3, where the uncertainties include statistical and systematic sources. The result excludes the no-mixing hypothesis with a probability corresponding to 9.1 standard deviations and represents the first observation of D0−¯¯¯D0 oscillations from a single measurement.